2019
DOI: 10.5530/fra.2019.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/ Nitrosative Stress, 8-OHdG and MMP-9: The Possible Co-Links and Early Sign of Arsenic Induced Urinary Bladder Carcinogenesis in Experimental Rats

Abstract: Background: Presently arsenicosis is considered as dangerous health issues including cancer. Urinary bladder is one of the common target organs for developing carcinogenesis by arsenic exposure due to accumulation of arsenic toxic metabolites in bladder. The mechanism involving urinary bladder carcinogenesis is still mysterious. Although there are multiple studies revealed about oxidative/nitosative stress, which plays main role for carcinogenesis, but no study evaluated the associated factor that linked with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For instance, a study found higher level of uranium while less arsenic in the Kushtia region of Bangladesh. [ 5 ] When aquifer occurs in newly deposited sediments, water with stagnant flow is at more risk to groundwater contamination. Earlier, it was found that arsenic and fluoride were the most dangerous natural contaminants, which were later shifted to manganese and uranium.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study found higher level of uranium while less arsenic in the Kushtia region of Bangladesh. [ 5 ] When aquifer occurs in newly deposited sediments, water with stagnant flow is at more risk to groundwater contamination. Earlier, it was found that arsenic and fluoride were the most dangerous natural contaminants, which were later shifted to manganese and uranium.…”
Section: Introductionmentioning
confidence: 99%